1985
DOI: 10.1063/1.1138197
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of volume-produced H− ions

Abstract: The results of an investigation on the extraction of volume-produced H -ions from severa] plasma sources, characterized by different magnetic multicusp configurations, as well as from a plasma source with no magnetic containment field, are presented. In all these configurations the extracted negative ion current can be increased and the electron current reduced by a suitable choice of the plasma electrode area and positive bias and of the extraction aperture area. This indicates that the variation of the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Biasing C also prevents secondary electron emission. 37 Increase in current ($10%) was observed when the extra þ18 V voltage was applied. The electron suppressor deflects most of the electrons and primarily allows the negative ions to reach the collector.…”
Section: Experimental Set-upmentioning
confidence: 96%
“…Biasing C also prevents secondary electron emission. 37 Increase in current ($10%) was observed when the extra þ18 V voltage was applied. The electron suppressor deflects most of the electrons and primarily allows the negative ions to reach the collector.…”
Section: Experimental Set-upmentioning
confidence: 96%
“…Bacal et al [8] found that one could optimize the extracted negative ion current not only in the tandem source, but also in a conventional and in a hybrid [9] multicusp plasma generator, and even in a plasma generator with no magnetic confinement (diffusion type). This occurred when the plasma electrode area was reduced to about 1/8 of the total cross section area of the source.…”
Section: Introductionmentioning
confidence: 99%
“…To explain these observations, different interpretations have been done: a) an E×B drift effect on negative charged particles, where the electric field E is due to positive grid bias, while the magnetic field B is the parallel to the surface filter; b) M. Bacal et al [4] suggested that due to the positive bias the plasma grid depletes the electron population near by and to compensate that depletion of electrons and to maintain the charge neutrality, negative ions from the volume plasma try to come there and increase the negative ion density; c) with no bias, the plasma potential in the bulk is positive relative to PG and the negative ions as well as the electrons are electrostatically trapped, i.e. the plasma is a potential well for them.…”
Section: Plasma Grid Bias Effectmentioning
confidence: 99%
“…In this region, gradients due to the plasma sheath (modified by a biased PG and by the presence of a magnetic filter) create forces strongly affecting not only the free flight but also collisional events involving H -ions produced in the bulk and on the PG surface. In fact, experiments and models [3][4][5][6][7] have shown that PG bias and magnetic filter play an important role for the enhancement of H -production and extraction (through the electron temperature and density and through the plasma potential variations).…”
Section: Introductionmentioning
confidence: 99%